1997
DOI: 10.1117/12.267840
|View full text |Cite
|
Sign up to set email alerts
|

<title>Spectral imaging applications: remote sensing, environmental monitoring, medicine, military operations, factory automation, and manufacturing</title>

Abstract: This paper reviews the activities at OKSI related to imaging spectroscopy presenting current and future applications of the technology. We discuss the development of several systems including hardware, signal processing, data classification algorithms and benchmarking techniques to determine algorithm performance. Signal processing for each application is tailored by incorporating the phenomenology appropriate to the process, into the algorithms. Pixel signatures are classified using techniques such as princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…This amount of valuable information can be used in critical image-based geoscience applications [3]. Unfortunately, the spatial resolution (SR) of remotely sensed spectral images is low, thus limiting the accuracy of the outcomes of spectral data applications [4][5][6][7], e.g., classification, unmixing, target and object detection, mineralogy, and change detection.…”
Section: Introductionmentioning
confidence: 99%
“…This amount of valuable information can be used in critical image-based geoscience applications [3]. Unfortunately, the spatial resolution (SR) of remotely sensed spectral images is low, thus limiting the accuracy of the outcomes of spectral data applications [4][5][6][7], e.g., classification, unmixing, target and object detection, mineralogy, and change detection.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to its capability for detailed scene representation, this technique has been widely adopted in many fields, including medical diagnosis, health care, remote sensing, and military operations [17,24]. Recently, it is found that various computer vision tasks, e.g., recognition, classification, and tracking, can benefit from incorporating the spectral information in tens or hundreds of bands [11,20,28].…”
Section: Introductionmentioning
confidence: 99%
“…Se puede solventar sin más que ubicar el sistema verticalmente y desplazar el material bajo el mismo en una sola dirección, tal y como hace una cinta transportadora en una planta de producción industrial. El empleo de la espectroscopia de imagen procede de aplicaciones militares y de sensado remoto [3]. Sin embargo, debido a sus características de operación no intrusivas ni destructivas, se preveía que podía dar solución a multitud de problemas en diferentes sectores industriales (agroalimentario, farmacológico, químico, etc.)…”
Section: Introductionunclassified
“…Sin embargo, debido a sus características de operación no intrusivas ni destructivas, se preveía que podía dar solución a multitud de problemas en diferentes sectores industriales (agroalimentario, farmacológico, químico, etc.) mejorando notablemente sus rendimientos económicos [3]. En aplicaciones industriales se utilizan tradicionalmente técnicas de visión o instrumentos que realizan medidas espectrales de manera puntual [4].…”
Section: Introductionunclassified